Characterizing Soybean Yield and Quality Response to Multiple Prophylactic Inputs and Synergies. (1st July 2016) - Mourtzinis, Spyridon; Marburger, David A.; Gaska, John M.; Conley, Shawn P.
Abstract : There is little peer‐reviewed information regarding prophylactic use of multiple inputs in soybean [ Glycine max (L.) Merr.] production systems as a way to increase seed yield and profitability. Therefore, the objective of this study was to examine the effect of multiple inputs on soybean yield and quality in Wisconsin (WI). Two separate studies were established from 2011 to 2013. The inputs examined included: trait [first (RR1) and second (RR2Y) generation Roundup Ready traits], rhizobia inoculant, fungicide seed treatment, foliar fertilizer, foliar insecticide, and foliar fungicide. In the first experiment, main effects and up to three‐way interactions were evaluated; whereas in the second experiment, all inputs were combined in a high‐management (i.e., intensive) treatment. In the first experiment, soybean yield was not consistently increased due to the used inputs. Trait and foliar fungicide use were significant factors with variable effect on soybean seed yield in three and four of the nine location‐years, respectively. The foliar insecticide effect varied between traits in three location‐years. The (rhizobia inoculant + fungicide seed treatment) × foliar insecticide × foliar fungicide interaction was a significant factor in three of the nine location‐years. None of the examined factors significantly increased yield across all location–years. In the second experiment, high‐management, trait, and their interaction did not consistently increase soybean yield, nor improved seed quality characteristics. Overall, these results suggest that WI growers should continue to use university‐developed integrated pest management principles for making input decisions instead of relying on prophylactic input applications for maximizing soybean yield and profitability. No sole input or interaction consistently increased soybean yield across site‐years. Intensive management had inconsistent and minimal effect on soybean yield. Growers should not rely on prophylactic input applications to maximize soybean yield.